Surat Pemblokiran adalah Objek Sengketa Peradilan Pajak (Studi Kasus Putusan Nomor: 142/G/2015/PTUN-JKT dan Putusan Nomor: 3/FP/2018/PTUN.JKT) - Elfrieda Anggi Basamarito; Anna Erliyana (Faculty of Law, Maranatha Christian University, 2022)
The position of the_tax dispute should not be the object_of a positive fictitious petition Article 53 of Law_Number 30 of 2014 Jo. Regarding Government Administration Juncto Law Number 11 of 2020 concerning Job Creation. The Tax Court is a special_judicial body within the State Administrative_Court. However, in its implementation, not all tax cases are addressed to the Tax Court. Judex Factie's decision in the positive fictitious application case number: 3/P/FP/2018/PTUN.JKT is correct and can be used as jurisprudence for non-tax court justice institutions, so according to normative juridical provisions it can be stated and confirmed that tax products issued by The taxation apparatus authorized in Indonesia is not included in the object regulated_in Article 53_of the Juncto Government Administration Law, Article 175 of the Job Creation Law, so that a positive fictitious application cannot be submitted to the_State Administrative_Court. Keywords: Tax Disputes, Tax Products, State Administrative Court